Dynamic planning approach of facility layout from industry perspectives: A systematic literature review - Isnaini Wildanul; Masruroh Nur Aini; Dharma IGB Budi (Production Engineering Archives)
A general classification of facility layout criteria, including the planning approach, material handling configuration, department area, layout generation approach, metaheuristic approach, and layout evaluation approach has been achieved through numerous reviews of facility layout. Based on dynamic planning approach research, the companies and industries as significant users of the facility layout, necessitate a more detailed and exhaustive review of the layout optimization (re-layout) strategy. However, that review remains incomplete. This paper aims to fill the gap between the industry’s practical needs and existing research on dynamic planning facility layout by conducting a literature review to identify various facility layout criteria and factors categorized by industry layout type, providing companies with clearer guidance for their layout decisions. A reference that provides a comprehensive analysis of the relevant characteristics, methods, and factors in determining layout types will be helpful to decision-makers as a strategy in facility layout. This literature review analyzed 44 articles from the Scopus database between 2014 and 2024. These articles were selected through a screening process from 1278 articles using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method which has proven effective in obtaining key articles on specific research topics. The results of this review present a classification of facility layout criteria based on layout type in industries complemented by the development of a checklist as an initial screening tool for the industry to optimize the layout. Further, it enhances the theoretical advancement of the dynamic planning approach by identifying areas for future investigation.